Inisiasi Tunas dan Pengakaran pada Kultur Jaringan Mawar (Rosa hybrida) cv Shangrila: Shoot Initiation and Rooting in Tissue Culture of Rose (Rosa hybrida) cv. Shangrila - Amelia Nurkhopipah; Nina Ratna Djuita; Ratnadewi, Diah (Jurnal Sumberdaya Hayati, 2026)
Rose (Rosa spp.) is a flowering plant belonging to the Rosaceae family. Roses are considered one of the most popular ornamental plants and are in high demand across various sectors. This popularity has led to a need for large-scale rose production, particularly hybrid cut flowers. This study aims to identify the optimal media composition for producing rose cv. Shangrila in large quantities and in a shorter time frame, independent of seasonal changes. The research employed a Completely Randomized Design (CRD), with nine replications for all treatments except for axillary shoot multiplication. The explants used were single-node stem segments. After sterilization, the explants were cultured on half-strength Murashige and Skoog (½ MS) medium without growth regulators for one week. This step was intended to evaluate the effectiveness of antibiotics used during the final stage of the sterilization process. Various concentrations of benzylaminopurine (BAP) were used during the shoot initiation stage, and bean sprout extract was incorporated into the medium during the shoot multiplication stage. The results showed that BAP at a concentration of 3 mg/L produced the highest number of shoots. The same media composition, without bean sprout extract (B3T0), yielded the highest percentage of shoot formation and the greatest shoot length. The optimal rooting medium was a 1:1 mixture of sand and vermiculite, supplemented with nutrients from a ½ MS solution without the addition of auxins.